An easy way to Pb(Mg1/3Nb2/3)O-3 synthesis - Cruz, Luísa P. (2002)
This work describes the very expeditious combustion synthesis of Pb(Mg1/3Nb2/3)O-3 perovskite powders from mixtures of Pb(NO3)(2), Mg(NO3)(2)(.)6H(2)O and Nb2O5, as cation precursors, and urea as fuel. The powders produced were characterized by XRD, SEM (EDS), and ICP and Nb-93 MAS NMR spectroscopies. Since, with this method, exposure to high temperatures is reduced to a minimum, the as-prepared combustion product shows no PbO loss. The % PMN in the as-prepared combustion powder is sensitive to, and increases with, the rise in the ignition temperature, and gets further improved upon calcination. However, the benefit of calcination, in terms of the reached maximum in the % PMN, becomes more modest when the ignition temperature is increased. Subsequent heat treatments of powder compacts in air (normal processing usually includes some kind of sintering step in order to improve crystallinity and densify the material), showed that over 90% Pb(Mg1/3Nb2/3)O-3 can be readily obtained at 870degreesC. (C) 2002 Elsevier Science Ltd. All rights reserved.